The Mediating Role of Coaching in the Relationship between Compensation, Job Involvement and Feedback on Employee Productivity in a Nigeria Higher Educational Institution - Adamu, Babale (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examined the mediating role of coaching in the relationship between compensation, job involvement and feedback on employee productivity in a Nigeria Higher Educational Institution. Organizations hope that their employees will be able to learn inspire and work towards improving their performance and productivity as well as organizational productivity as it is only by increasing productivity, employees can obtain better wages, salaries, working conditions and larger employment opportunities. Nevertheless, the constantly changing attitude of employees’ job has negatively affected the traditional employment engagements that offer an employee a sense of organizational commitment, involvement, and support in their jobs. With reduced organizational commitment and job involvement, feedback and support in form of coaching, employee productivity to the organization weakens. In spite of this, organizations most especially the Nigeria’s university education employees have been characterized by unpredictable and standardized way of measuring their productivity. This paper attempts to investigate the mediating role of coaching on job related factors of compensation, job involvement and feedback towards employee productivity on a total population of 1445 employees who are working under FUD, Jigawa State, Nigeria. An aggregate of 900 copies of questionnaire were distributed to the respondents. However, 583 questionnaires were finally retained for analysis from a total 691 questionnaires that were collected back from the respondents. PLS-SEM Bootstrap, Sobel test were the procedures and techniques employed in this study to assess and evaluate the statistical significance of relevant path coefficients as well as exploration of challenges faced by employees in their drive towards productivity. The findings disclosed that the extent to which organizational employees are provided with compensation, fully involved, and with regular feedback, and supported by both supervisors and peers in their jobs in terms of coaching would gear them to be keen in making persistent and intense efforts towards improving their performance as well as productivity. In addition, this study highlighted some of the challenges faced by employees towards employee productivity. This study also demonstrated that coaching is a fundamental key element in the employee productivity resultant effects. Hence, the basic principle of the coaching approach is that performance will be fully enriched. Most especially, if high levels of the understudied factors from the organization and employee as well as the clearly defined organizational goals and objectives are present. Keywords: Compensation, job involvement, feedback, coaching, employee productivity